The Effect of SNAP and School Food Programs on Food Security, Diet Quality, and Food Spending: Sensitivity to Program Reporting Error. (26th April 2019) - Kang, Kyung Min; Moffitt, Robert A.
Abstract : There is an extensive research literature on the effects of the Supplemental Nutrition Assistance Program (SNAP) on food‐related outcomes which has shown somewhat mixed results but generally favorable effects. However, most of the research has used data sets whose information on SNAP participation is gathered from responses on household surveys, and such responses are subject to reporting error. This study uses the National Household Food Acquisition and Purchase Survey data set to examine the effect of reporting error on food‐related outcomes, for that data set contains information on SNAP participation gathered from government administrative records. Our analysis shows that the degree of reporting error is small and has little effect on the estimated impact of participation in the SNAP program on food security, diet quality, and food spending. A supplemental analysis of the effect of school food programs likewise shows no difference in using survey or administrative data in the analysis.